Effect of combined dexmedetomidine with ropivacaine in transversus thoracis plane block on surgical stress response during cardiopulmonary bypass surgery: a randomized controlled trial - Huang, Lian; Chen, Ying; Xu, Xiaohua; Zeng, Fanpei; Li, Chuntian; Fu, Hangxiang (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo examine how patients having open heart surgery under cardiopulmonary bypass (CPB) react to surgical stress following bilateral transversus thoracis plane (TTP) block with ropivacaine improved by dexmedetomidine (DEX).MethodsThree groups of sixty patients (26M/34F, ASA II–III, 18–65 years old) slated for elective CPB heart surgery were randomly assigned: general anesthesia alone (Group C), TTP (ropivacaine) combined with general anesthesia group (Group R), or TTP (ropivacaine + DEX) combined with general anesthesia group (Group RD). Primary outcomes measured serum cortisol levels at five perioperative phases, while the secondary outcomes included glucose/C-reactive protein (CRP) levels, Numeric Rating Scale (NRS) pain scores postextubation, 48-hr sufentanil consumption, patient-controlled analgesia (PCA) demand frequency, rescue analgesia rates, mechanical ventilation duration, ICU stay, and complications.ResultsAt 24 h postoperatively, RD and R groups exhibited statistical lower serum cortisol levels compared to controls (p < 0.05), with parallel glucose reductions. However, the CRP level increased significantly. NRS scores in RD/R groups were significantly lower than controls at 0 h, 6 h, and 12 h postextubation (p < 0.05), and the RD group maintained superior analgesia vs. both groups at 24 h. RD and R groups demonstrated significant reductions for 48-h sufentanil consumption vs. controls, and RD group showed less total sufentanil consumption vs. R group. Besides, both mechanical ventilation duration and ICU stay were shortened by serval hours compared to control. Significant reductions in the count of effective analgesic pump compressions were observed in groups R and RD compared to the control group. Moreover, rescue analgesia rates were 55%, and 15% lower in RD vs. R and Control groups, respectively (p = 0.031). However, no intergroup differences occurred pulmonary complications.ConclusionDEX-enhanced TTP blockade may contribute to attenuating the stress response, optimizing analgesia, and improving early postoperative recovery parameters in CPB cardiac surgery through opioid-sparing mechanisms and sympatholytic effects, demonstrating clinical viability within Enhanced Recovery After Surgery (ERAS) protocols.Clinical Trial Registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2400085899.